Embedding Open Access into the European Landscape – the Contribution of LIBER - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
This paper continues an earlier published history of the OAI Workshops, organised under the aegis of the LIBER Access Division, in CERN Geneva. It discusses the OAI5 Workshop, held on 18-20 April 2007, which underlines the emerging importance of Open Access to support information provision and exchange across Europe.